Penggunaan Metode Tutor Sebaya Untuk Meningkatkan Aktivitas dan Hasil Belajar Materi Resistor - Eny Haryanti Fuadi (Universitas Pancasakti Tegal, 2020)
This study aims to increase the activity and learning results of resistor material in class X students TAV1 SMK Negeri 1 Adiwerna academic year 2016/2017. The research method used is classroom action research by carrying out two cycles and each cycle consists of planning, action, observation and reflection. From the results of the study the use of peer tutoring methods there was an increase in learning activities of students from an average of 73.95% in the first cycle to 87.49% in cycle II. Students' learning outcomes increased from the initial condition of the percentage of the complete number of learners by 56.25% increased in the complete cycle I studied 75% and at the end of cycle II to 87.50%. Classical learning outcomes are complete (beyond classical completeness) of 80%.